Measuring Financial Integration: The Case of The Indian ‎Stock Market and Global Trends - Devaki, M.; Shetty, Sharan Kumar; Popescu, Virgil; Birau, Ramona; Margaritescu, Stefan; Vidhya, P.; Renukadevi, D.; Manochithra, P.; Devaram, N. (International Journal of Accounting and Economics Studies, 2025)
Globalization has significantly increased the interdependence of financial markets, making the study of stock market integration highly ‎relevant. This research investigates the integration of the Indian stock market (CNX Nifty) with major global indices, including the New ‎York Stock Exchange (NYSE), NASDAQ, and the Shanghai Stock Exchange (SSE), over the period from January 2022 to December ‎‎2024. Employing statistical techniques such as cointegration tests and Granger causality, the study analyzes co-movements, interdepend‎encies, and causal relationships among these markets. The findings reveal long-term cointegration between the CNX Nifty and the global indices, indicating that these markets share a stable long-term relationship despite short-term fluctuations. Granger causality analysis ‎shows that the CNX Nifty has predictive influence over the NYSE but not over NASDAQ, while a bidirectional relationship exists with ‎the SSE Composite. These results provide valuable insights for investors and policymakers, highlighting the increasing significance of ‎India’s market in the global financial system and informing strategies for risk management and investment opportunities‎.